Close encounters of the three morphs: Does color affect aggression in a polymorphic lizard?. Issue 4 (7th March 2021) - Scali, Stefano; Mangiacotti, Marco; Sacchi, Roberto; Coladonato, Alan Jioele; Falaschi, Mattia; Saviano, Luca; Rampoldi, Marina Giulia; Crozi, Matteo; Perotti, Cesare; Zucca, Francesco; Gozzo, Elisabetta; Zuffi, Marco Alberto Luca
Abstract: Color polymorphism is genetically controlled, and the process generating and maintaining morphs can affect speciation/extinction rates. Color badges are useful signals in intraspecific communication because they convey information about alternative strategies and can potentially decrease unnecessary conflicts among different color morphs. Competition and aggressive interactions among color morphs can contribute to polymorphism maintenance. This could lead to an uneven spatial distribution of morphs in a population because the local frequency of each morph establishes the intensity of the competition and the fitness of each male. We used a polymorphic lizard, Podarcis muralis, to assess if aggression varies among morphs under two contrasting hypotheses: a heteromorphic versus homomorphic aggression. We used laboratory mirror tests after lizard color manipulation, and we verified the consistency of results with an analysis of the spatial distribution of morphs in a wild population. Both the experiments confirmed that aggression is more common during homomorphic than heteromorphic contests. The adoption of alternative behavioral strategies that minimize risks and costs could facilitate the stable coexistence of the phenotypes and reduce competition. A bias in aggression would advantage rarer morph, which would suffer less harassment by common morphs obtaining a fitness advantage. This process would be negatively‐frequency‐dependent and would stabilize polymorphism, possibly contributing to sympatric speciation.